Silicon on C:N:P stoequiometry and nutritional efficiency of sugarcane grown under water deficit in three tropical soils - Costa, Milton Garcia [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The benefit of silicon (Si) in the lives of the plants is undeniable, mainly the physiological and biochemical benefits, mainly in sugarcane plants in conditions of water deficit. However, little was understood about the impact of this beneficial element on modifying the homeostatic balance of carbon (C) – nitrogen (N) – phosphorus (P) and on the nutritional efficiency of sugarcane plants and whether these changes are enough to alter crop dry mass production under different soil conditions in the tropics. In order to broaden the understanding of the benefit of Si, the present study was carried out, aiming to evaluate the supply of Si, via fertirrigation, is sufficient to modify the homeostatic balance of C:N:P and increase the nutritional efficiency of sugarcane plants under water deficit in three tropical soils. For this, three experiments were carried out with pre-sprouted seedlings of sugarcane in three tropical soils (Dystrophic Red Latosol, Eutrophic Red Latosol and Quartzarenic) under controlled conditions in a greenhouse in two cycles of 150 days (1st cycle and 2nd cycle). Silicon was supplied via fertigation at a concentration of 1.8 mM every two days using the stabilized sodium silicate source with sorbitol. Biological losses caused by water deficit in sugarcane plants are related to the homeostatic imbalance of C:N:P, causing reductions in nutrient use efficiency and directly impacting dry mass biosynthesis. Silicon becomes a viable agronomic alternative in sugarcane crops with water restriction, reducing biological losses due to water deficit, modifying the homeostatic balance of C:N:P, improving the efficiency of use of these nutrients and improving the plant performance. The use of Si in sugarcane cultivation without stress was also efficient in improving plant performance, alternating the homeostatic nutritional balance, increasing the efficiency of use of C, N and P and increasing the production of dry mass of leaves and stems. The responses of sugarcane plants to Si application are limited depending on the type of cultivation soil, altering the intensity of responses to the benefits of the beneficial element. The strategic use of fertigation with Si in a water deficit regime becomes more advantageous in tropical soils with low availability of Si in the soil solution, such as the Quartzarenic Neosol. The perspective of the research is that Si can contribute to the sustainable cultivation of sugarcane in tropical soils in irrigated regions or under a regime of water deficit.

O benefício do silício (Si) nas vidas das plantas é incontestável, principalmente os benefícios fisiológicos e bioquímicos, principalmente em plantas de cana-de-açúcar em condições de déficit hídrico. Entretanto, pouco se compreendia do impacto deste elemento benéfico em modificar o equilíbrio homeostático do carbono (C) – nitrogênio (N) – fosforo (P) e na eficiência nutricional das plantas de cana-de-açúcar e se essas alterações são o suficiente para alterar a produção de massa seca da cultura nas diferentes condições de solos nos trópicos. Para ampliar a compreensão do benefício do Si, realizou-se o presente estudo, objetivando-se avaliar o suprimento do Si, via fertirrigação, é suficiente para modificar o equilíbrio homeostático do C:N:P e incrementar a eficiência nutricional de plantas de cana-de-açúcar em déficit hídrico em três solos tropicais. Para isso, realizou-se a instalação de três experimentos com mudas pré-brotadas de cana-de-açúcar em três solos tropicais (Latossolo Vermelho Distrófico, Latossolo Vermelho Eutrófico e Neossolo Quartzarênicos) em condições controladas em casa de vegetação em dois ciclos de 150 dias (1º ciclo e 2º ciclo). O silício foi fornecido por via fertirrigação na concentração de 1.8 mM a cada dois dias utilizando a fonte de silicato de sódio estabilizado com sorbitol. As perdas biológicas causadas pelo déficit hídrico nas plantas de cana-de-açúcar estão relacionadas ao desequilíbrio homeostático de C:N:P, causando reduções na eficiência de uso de nutrientes e impactando diretamente na biossíntese de massa seca. O silício torna-se uma alternativa agronômica viável em cultivos de cana-de-açúcar com restrição hídrica, reduzindo as perdas biológicas por déficit hídrico, modificando o equilíbrio homeostático de C:N:P, melhorando a eficiência de uso desses nutrientes e melhorando o desempenho da planta. A utilização de Si no cultivo de cana-de-açúcar sem estresse também se mostrou eficiente em melhorar o desempenho das plantas, alternando o equilíbrio nutricional homeostático, aumentando a eficiência de uso de C, N e P e aumentando a produção de massa seca de folhas e caules. As respostas das plantas de cana-de-açúcar à aplicação de Si são limitadas dependendo do tipo de solo de cultivo, alterando a intensidade das respostas aos benefícios do elemento benéfico. O uso estratégico da fertirrigação com Si em regime de déficit hídrico torna-se mais vantajoso em solos tropicais com baixa disponibilidade de Si na solução do solo, como o Neossolo Quartzarênico. A perspectiva da pesquisa é que o Si pode contribuir para o cultivo sustentável da cana-de-açúcar em solos tropicais em regiões irrigadas ou sob regime de déficit hídrico.
Silício na estequiometria C:N:P e eficiência nutricional de cana-de-açúcar cultivada sob déficit hídrico em três solos tropicais
Keywords: Saccharum officinarum L.; Beneficial element; Homeostatic balance of C:N:P; Water stress; Abiotic stress; Elemento benéfico; Equilíbrio homeostático de C:N:P; Estresse hídrico; Estresse abiótico; Fertirrigação; Fertigation